Spoiler alert : a novel - Dade, Olivia (Avon, an imprint of HarperCollinsPublishers, 2020)
When her viral fan-fiction leads to a disastrous publicity-stunt date with her celebrity crush, a talented plus-sized writer discovers that the actor secretly writes his own popular fan-fiction against studio rules.